CREATION OF MULTILAYERED KERATINOCYTE SHEET ON COLLAGEN FROM HUMAN AMNIOTIC MEMBRANE - Hà, Trần Lê Bảo; Toại, Trần Công; Sơn, Hoàng Nghĩa (Vietnam Journal of Biotechnology, 2011)
Epidermis composed of terminally differentiated stratified squamous epithelium is the outermost layer of the skin. The epidermis is the major barrier protect the body from inhospitable environment factors such as biological, chemical, physical factors. Epidermis which consists of the multilayered keratinocytes could be created in vitro for the freatment of acute burn injuries and chronic wounds. In this study, the multilayered keratinocyte sheets were created from the adult human keratinocytes and the amniotic collagen membrane. Human keratinocytes were isolated, cultured, amplified in seram free medium. Collagen membrane was derived from human amniotic membrane of which the epithelium was removed and evaluated by HE staining. After subcultured on collagen membrane, keratinocytes were stimulated for proliferation and differentiation to create multilayer by airlifting. The multilayered keratinocyte sheet characteristics were evaluated by using RT-PCR and immunohistochemistry. The results showed that epithelial cells were removed completely from the human amniotic membrane by enzyme and mechanical treating. Keratinocytes proliferated and formed 4 - 5 layers on collagen. They also expressed some differentiation and proliferation markers at 7 days after airlifting. The keratinocytes which were positive with proliferative marker (p63) lied closely on the collagen membrane and upper ofthe cells differentiated